Art andCommunication: Conflict and Reconstruction for Autonomous Identity - Inatci, Umit (Online Journal Communication & Media Technologies-Ojcmt, 2015)
This essay focuses on the relational embodiment of art & communication that, it is fair to say, that it implicates problematic crossroads between memory and contemplation. If we see art as, I believe one should, as inter-subjective communication emanating from the primary necessities, which in turn arise from ontological concerns then we should pay attention to the relationship between art and communication. This essay is structured in three pats dealing with different instinctive and notional aspects of the subject. 1/Attention-Intention Relation. 2/Inside-Outside-Presence. 3/Memory-VisualCulture-Notion.
Keywords: Art; Communication; Visual Culture; Memory; Presence